Primary leiomyosarcoma of the skin: a comprehensive review on diagnosis and treatment - Zacher, Martina; Heppt, Markus V.; Brinker, Titus Josef; Hayani, Kinan M.; Flaig, Michael J.; Berking, Carola (Medical oncology, 2018)
Sarcomas are a heterogeneous group of mesenchymal tumors which can affect bone and soft tissue. Leiomyosarcoma (LMS) is a rare subtype localized to the skin or subcutaneous tissue. Due to the heterogeneity of sarcomas, reviews and guidelines with an in-depth focus specifically on primary LMS of the skin are sparse. This article is intended to provide an up to date and systematic overview on diagnosis, treatment, and surveillance of this rare entity to provide a framework for decision making and management for dermato-oncologists. We discuss novel treatment options for advanced disease such as targeted therapy with kinase inhibitors and immune checkpoint blockade which may improve the prognosis even in advanced stages of LMS.
Gesehen am 10.03.2020